The effect of storage conditions on ethanol content of kombucha tea - Sharizainor Sharina, Mohamed Shariff; Azizan, Ramli; Nazikussabah, Zaharudin (AIJR Publisher, 2023)
Ethanol is one of the alcohol compounds commonly found in food and beverages. Some of the food and beverage products sold in the market contain ethanol. In accordance with that, the objective of this research was to analyse the ethanol content of kombucha tea which is stored at a certain duration and temperature. The research experiment used commercial and homemade kombucha teas. The test was performed at 2 contact temperatures, 8°C (chiller) and 28°C (room temperature) for a duration of 4 weeks. Each sample was analysed for ethanol content, every 1 week using a gas chromatograph coupled with a single quadrupole mass spectrometer (GC-FID). The results demonstrate that storage temperature significantly influences ethanol production, with higher temperatures yielding elevated ethanol content. The ethanol content of commercial kombucha tea stored for 28 days at 28°C was the highest ethanol content (3.43±0.06% ABV). The lowest ethanol content was found in kombucha green tea (1.55±0.11% ABV) which was kept in the chiller (8°C) for the duration of 28 days. It was found that storage temperature and duration play important roles in the concentration of ethanol content. These findings provide producers and regulators with valuable insights for optimising storage practises, promoting halal compliance, and ensuring food safety while preserving fermented beverage’s quality and flavour.